A High-Power Hybrid-Strip Monopulse Antenna Array for Secondary Surveillance Radars - Alieldin, Ahmed; Eid, Alla M.; Salama, Amgad A. (Journal of Electronics and Electrical Engineering, 2025)
This paper proposes a novel design of a high-power monopulse antenna array for secondary surveillance radars (SSR) utilized in air traffic control (ATC) systems. A novel technique of hybrid-strip (HS) technology is applied to the antenna array (composed of stripline for the feeding network and microstrip for the antenna elements) to minimize the effect of the transition between the feeding network and antenna elements. The antenna array consists of two identical mirrored halves. Each half is 2 rows × 6 columns. The antenna elements are rectangular microstrip patches with shorting vias while the feeding network is composed of a combination of synthesized stripline dividers/combiners. A backfill antenna along with a control network is utilized to achieve the monopulse technique and sidelobe suppression. The control network is a stripline rat race attached to couplers. The antenna array achieves an excellent monopulse performance at the uplink (1030 MHz) and the downlink (1090 MHz) with a return loss better than 15 dB, a realized gain of 22.2 dBi and two independent Sum and Diff channels with a Sum-to-Diff ratio of 30 dB at the antenna boresight. The antenna array can handle a peak power of up to 2.7 MW for long-range traffic detection and control. Such performance makes the proposed antenna array a perfect candidate for Secondary Surveillance Radar.